Women leading education across the continents. - Sobehart, Helen C., 1948- (Rowman & Littlefield Education, 2009)
Women Leading Education across the Continents is the first collection of research about and stories of women in basic and higher education leadership from every region of the globe. The chapters are authored by scholars representing every continent.